GENE EXPRESSION ANALYSIS TO PREDICT PATIENT RESPONSE TO CHEMOTHERAPY - Loso Judijanto; Rafiullah Amin; Roya Zahir (Journal of Biomedical and Techno Nanomaterials, 2025)
Chemotherapy is a cornerstone of cancer treatment, yet patient responses vary significantly. Understanding the molecular basis of this variability is crucial for optimizing therapy. To predict patient response to chemotherapy using gene expression analysis, aiming to improve personalized treatment strategies. A prospective cohort study involving high-throughput RNA sequencing and microarray analysis was conducted on tumor biopsies and blood samples from patients undergoing chemotherapy. Differentially expressed genes were identified and correlated with treatment outcomes. Gene expression profiles of ABCB1, TP53, BRCA1, ERBB2, and BCL2 were found to significantly predict chemotherapy response. Patients with high expression of these genes showed better treatment outcomes. In vitro and in vivo models validated these findings, confirming the predictive power of these gene signatures. Gene expression analysis provides valuable insights into predicting chemotherapy response, facilitating personalized cancer treatment. Further clinical trials are necessary to validate these biomarkers and develop accessible diagnostic platforms.